2020
DOI: 10.1080/09506608.2020.1825175
|View full text |Cite
|
Sign up to set email alerts
|

Cryomilling as environmentally friendly synthesis route to prepare nanomaterials

Abstract: The milling of materials at cryogenic temperature has gained importance both in academic as well as the industrial community in the last two decades, primarily because of significant advantages this technique as compared to milling at room temperature; environmental friendly nature, cost-effectiveness, rapid grain refinement, less contamination, and large scale production capability of various nanomaterials. Scientifically, milling at cryo-temperature exhibits several distinct material related phenomena; suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 289 publications
0
20
0
1
Order By: Relevance
“…In relation to Green Chemistry process, relatively recent article 73 evaluated technological aspects of cryomilling such as its environmental impact, scale-up potential, and potential applications. It has been shown that from the point of Green Chemistry principles, the cryomilling is an eco-friendly process, and that the large-scale cryogrinding can be utilized in different applications, especially those that involve temperature-sensitive materials (i.e., drug delivery vehicles, matrices loaded with pesticides, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to Green Chemistry process, relatively recent article 73 evaluated technological aspects of cryomilling such as its environmental impact, scale-up potential, and potential applications. It has been shown that from the point of Green Chemistry principles, the cryomilling is an eco-friendly process, and that the large-scale cryogrinding can be utilized in different applications, especially those that involve temperature-sensitive materials (i.e., drug delivery vehicles, matrices loaded with pesticides, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The only by-product of the process is nitrogen gas which can be directly released into the air, causing no harm to the environment. The presence of a cryogenic environment also prevents the recovery and recrystallization of refined grains [ 25 ]. This ultimately provides a superior crystallite size reduction and significant grain refinement compared to other NC material synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…The fibers are dispersed at nanoscale, thus, a significantly less filler fraction is needed as compared to the conventional reinforcing materials, while the properties of composites are markedly improved [ 11 , 12 ]. To minimize the environmental health and safety concerns, the sustainable and environmentally friendly development of nanomaterials is highly desired [ 13 , 14 ]. One of the most promising strategies for the sustainable development involving nanotechnology is the isolation of nanomaterials from low-cost, abundant, renewable and biodegradable resources [ 15 ].…”
Section: Introductionmentioning
confidence: 99%